Key Role of Left Atrial Appendage during Redo Ablation in a Case of Long-Standing Persistent Atrial Fibrillation. (19th June 2020) - Wu, Shaohui; Zou, Guangchen; Liu, Xu; Jiang, Weifeng; Qin, Mu; Zhang, Daoliang
Abstract : Extrapulmonary vein focal sources have been recognized as the source of atrial fibrillation in some cases, and empiric electric isolation of the left atrial appendage has been proposed for long-standing persistent atrial fibrillation by some. Here, we present a case of redo ablation of long-standing persistent atrial fibrillation in which the left atrial appendage played a key role in maintaining AF during ablation, and atrial fibrillation was terminated by electrical isolation of the LAA. During the ablation, a rare phenomenon of half of the atria in atrial fibrillation while the other half of the atria in atrial flutter was seen.